Impacto da Fadiga, Depressão e Ansiedade na Cognição em Doentes com Esclerose Múltipla - Isabel Soares de Albergaria Velho Cabral (2024)
Multiple sclerosis (MS) is a chronic, neurodegenerative, inflammatory, and autoimmune disease characterized by demyelination of the central nervous system (CNS) (Oreja-Guevara et al., 2019). This condition typically manifests in young adults and can result in physical disability, cognitive impairment, and a diminished quality of life (McGinley et al., 2021). Several factors can impact cognitive performance in patients and should be considered in the assessment and management of neuropsychological alterations, particularly depression, anxiety, and fatigue (Portaccio & Amato, 2022). The primary objective of the present study is to explore whether these three variables exert a direct influence on cognitive performance, specifically in terms of memory and processing speed. To this end, a sample of 242 patients diagnosed with Relapsing-Remitting Multiple Sclerosis at the São João University Hospital Center (CHUSJ) was analyzed. The results indicate that fatigue and depression show a significant association with cognitive impairment, particularly in processing speed. Conversely, no statistically significant relationship was identified between anxiety and cognitive impairment. However, there is a strong correlation among the variables of fatigue, depression, and anxiety. Age and education also play an important role in cognitive performance. Given the prevalence of cognitive impairment in individuals with MS, early and annual neuropsychological assessments are recommended to implement preventive measures against more pronounced decline, ultimately improving the quality of life of patients. Keywords: Relapsing-Remitting Multiple Sclerosis; Neuropsychology; Cognitive Function; Fatigue; Depression; Anxiety.